Spectrophotometric determination of furosemide in pharmaceutical formulations – A didactic approach, from practice to theory - da Silva Neto, Adalberto Alves; Pacheco, Wagner Felippe; Semaan, Felipe Silva (Eclética Química, 2014)
Spectrofluorimetric determination of furosemide in pharmaceutical – a didactical approach, from theory to practice. The purpose of this paper is to present a complete possible application of simple strategies to teach basic concepts of molecular spectrofluorimetry. An ordinary anti-hypertensive drug was chosen in order to demonstrate many theoretical and practical aspects of spectrofluorimetric determinations in an accurate, precise, and inexpensive analytical lab practice. Historical aspects and fundamentals, and their contextualization for students, are also presented, being some experiments described using cheap samples.